2010
DOI: 10.1136/bmj.c117
|View full text |Cite
|
Sign up to set email alerts
|

Is a subgroup effect believable? Updating criteria to evaluate the credibility of subgroup analyses

Abstract: pointsSeven existing criteria help clinicians assess the credibility of putative subgroup effects on a continuum from "highly plausible" to "extremely unlikely" We suggest four additional criteria: subgroup definition on the basis of baseline characteristics, independence of the subgroup effect, a priori specification of the direction of the subgroup effect, and consistency across related outcomes We propose a re-structured checklist of items addressing study design, analysis, and context

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
513
1
16

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 594 publications
(538 citation statements)
references
References 34 publications
8
513
1
16
Order By: Relevance
“…The subgroup effect and its direction was specified a priori, the difference between subgroups was relatively large (about 21 hours), and chance seems an unlikely explanation (P<0.001). Credibility of the effect, however, is undermined34 as the effect modification is suggested by comparison between rather than within studies, and we found no similar difference in any other outcome. In addition, the only randomised controlled trial that compared oral and intramuscular treatment with dexamethasone reported no significant difference in any outcome 25…”
Section: Discussioncontrasting
confidence: 57%
“…The subgroup effect and its direction was specified a priori, the difference between subgroups was relatively large (about 21 hours), and chance seems an unlikely explanation (P<0.001). Credibility of the effect, however, is undermined34 as the effect modification is suggested by comparison between rather than within studies, and we found no similar difference in any other outcome. In addition, the only randomised controlled trial that compared oral and intramuscular treatment with dexamethasone reported no significant difference in any outcome 25…”
Section: Discussioncontrasting
confidence: 57%
“…Furthermore, even when the analysis of a particular factor produces a β W that is statistically and clinical important, there may still be debate about whether the factor is a genuine causal modifier of treatment effect. Sun et al 58. provide guidance for identifying whether differences in subgroups are believable, and this includes consideration of biological plausibility.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that a uniform approach4, 21 and greater degree of rigour may be required in assessing the value of these studies prior to publication, incorporation into clinical practice guidelines, and by extension, clinical practice itself.…”
Section: Concluding Thoughtsmentioning
confidence: 99%